Sand addition promotes gharial nesting in a regulated river‐reservoir habitat - Gaurav Vashistha (Wiley, 2021)
Abstract The gharial (Gavialis gangeticus) is a critically endangered, long‐snouted crocodilian, endemic to the Indian sub‐continent. Today, the species' distribution and numbers have reduced by more than 95% in all the large rivers where it was formerly abundant. Living upstream in a reservoir dammed in 1976, the Katerniaghat gharial population has continued to nest along the Girwa River, subject to seasonal flooding in recent decades. In 2010, a natural flood upstream in Nepal resulted in a permanent reduction in the mainstream river flow. As a consequence of reduced flow, the formerly open sand banks and mid‐river islands have converted gradually to riverbanks with woody vegetation. Coincident with the increased vegetation growth, gharial nesting sites and nest numbers declined by more than 40% by 2018. In an attempt to reverse the observed decline in nesting, we intervened with vegetation removal (VR) in 2019 and sand addition (SA) in 2020, to augment available nesting opportunities at previous and potential nesting locations. The number of nests increased with SA (n = 36 in 2020) but decreased with VR (n = 19 in 2019), relative to the prior year without intervention (n = 25 in 2018). Furthermore, hatching success increased significantly to 93% with SA, compared to 63% in VR. Creating an artificial sand bank required approximately one‐third work hours and cost much less than removing vegetation. Substrate temperatures in and around nests approximated the viable incubation range (29–33.5°C) when vegetation is absent, but were lower in sites covered with woody vegetation and/or dense, high grass. Our study indicates that gharial will respond favourably to newly created sand banks that provide open, sandy riverside nesting areas, in contrast to cut‐over sites with dense vegetation removed. Finally, we note that this strategy of augmenting nesting sites is only an interim attempt to solve the ‘nesting site’ dilemma for the river‐adapted gharial. Landscape‐level solutions related to resumption of seasonal flooding, and particularly natural flow regimes that are dynamic, rather than steady, will likely be needed to avoid local extirpation of gharial in river‐reservoir habitats.